Pemberdayaan Masyarakat Kampong Tenun Berbasis E-Commerce - Khusnul Khatimah; Khoirul Amin; Yeni Rahmawati (Journal of Empowerment and Community Service (JECSR), 2022)
Community Service Program in collaboration with the Weaving Group of Gg. Muharram Weaving Village, Samarinda. The conduct of commercial activities, particularly the marketing side, continues to be conducted in a conventional manner. Thus, the scope of marketing is still quite restricted, and the business being conducted has not been able to flourish. Consequently, socialising and e-commerce training are proposed as a remedy to partner issues. The digital/online marketing socialisation exercise has achieved the desired outcome, namely an improvement in awareness of the significance of online marketing, such that following the socialisation, participants are able to articulate the significance of online marketing